Morphological variability and cluster analysis of 16 bambara groundnut (Vigna subterranea) genotypes - MUHAMMAD FAUZAN FARID AL HAMDI; SATRIYAS ILYAS; ABDUL QADIR; SEAN MAYES (Society for Indonesian Biodiversity, 2024)
Abstract. Hamdi MFFA, Ilyas S, Qadir A, Mayes S. 2024. Morphological variability and cluster analysis of 16 bambara groundnut (Vigna subterranea) genotypes. Biodiversitas 25: 97-106. Identifying morphological and germination characters in bambara groundnut (Vigna subterranea (L.) Verdc.) is important to determine the advantages and disadvantages of several genotypes. This study aimed to identify the characteristics of 16 bambara groundnut genotypes based on morphological markers, NDVI score, and germination variables. This study was conducted in Sumedang, West Java, Indonesia in March-July 2018. The experiment was arranged in a randomized complete block design with one factor: genotype, which consisted of 16 genotypes originating from Indonesia and Africa. The NDVI score did not affect the yield produced. Tiga Nicuru, DodR-R II, M-14 Gresik, Black Sukabumi, and Black Madura were the genotypes with the highest germination speed, while LunT was the lowest. Cluster analysis showed that bambara groundnut genotypes are classified into 4 clusters. The first cluster belongs to Sumedang and Sukabumi, the second belongs to Gresik, Madura, and Tasikmalaya, the third comes from West Africa (LunT and Tiga Nicuru), and the fourth comes from East Africa (IITA 686 and DodR-R II) and Southern Africa (S 19-3, Uniswa R and Uniswa R/G). The low similarity (28%) between genotypes from Indonesia and Africa shows that there are many differences in morphological characteristics. This high diversity is beneficial for creating superior cultivars.